2014
DOI: 10.1099/vir.0.064923-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mutational analysis of the helicase domain of a replication initiator protein reveals critical roles of Lys 272 of the B′ motif and Lys 289 of the β-hairpin loop in geminivirus replication

Abstract: Replication initiator protein (Rep) is indispensable for rolling-circle replication of geminiviruses, a group of plant-infecting circular ssDNA viruses. However, the mechanism of DNA unwinding by circular ssDNA virus-encoded helicases is unknown. To understand geminivirus Rep function, we compared the sequence and secondary structure of Rep with those of bovine papillomavirus E1 and employed charged residue-to-alanine scanning mutagenesis to generate a set of singlesubstitution mutants in Walker A (K227), in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…The betasatellite depends on the helper virus genome and is transcribed to produce the βC1 protein, which functions as a pathogenesis determinant and suppressor of RNAi [ 12 , 13 ]. Of these proteins encoded by the geminivirus genome, replication initiator protein (Rep, encoded by ORF C1) is highly conserved both structurally and functionally across the Geminiviridae family [ 14 , 2 , 15 ]. Rep is a multitasking protein that is indispensable for the replication of the viral genome and confers virus-specific recognition of its cognate origin of replication [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The betasatellite depends on the helper virus genome and is transcribed to produce the βC1 protein, which functions as a pathogenesis determinant and suppressor of RNAi [ 12 , 13 ]. Of these proteins encoded by the geminivirus genome, replication initiator protein (Rep, encoded by ORF C1) is highly conserved both structurally and functionally across the Geminiviridae family [ 14 , 2 , 15 ]. Rep is a multitasking protein that is indispensable for the replication of the viral genome and confers virus-specific recognition of its cognate origin of replication [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that during synthesis of progeny strands, Rep helicase activity unwinds the dsDNA intermediate in the 3′–5′ direction using nucleotide triphosphates as an energy source (Choudhury et al 2006; Clerot and Bernardi 2006). Walker A motif forms part of the ‘P-loop’ structure in the NTP-binding domain that facilitates ATP recognition and binding with a conserved lysine residue (Desbiez et al 1995; Timchenko et al 1999; Choudhury et al 2006; Clerot and Bernardi 2006; Rosario, Duffy, and Breitbart 2012; George et al 2014). The Walker B of genomoviruses is predominantly ‘uuDDu’ (Fig.…”
Section: Conserved Sequence Motifs In the Genomoviridaementioning
confidence: 99%
“…The hydrophobic residues in Walker B motif contribute to ATP binding and are essential for ATP hydrolysis, whereas the one in motif C (Fig. 6; Supplementary Data S1) interacts with the gamma phosphate of ATP and the nucleophilic water molecule via a conserved asparagine residue (Choudhury et al 2006; George et al 2014). …”
Section: Conserved Sequence Motifs In the Genomoviridaementioning
confidence: 99%
“…1A) which makes it a potential protein to regulate various cellular and molecular functions. Proteins containing such AAA domain have been shown to involved in DNA replication, transcription control, degradation of protein, membrane fusion, microtubule regulation, signal transduction and the regulation of gene expression3536. Majority of reports highlighting the specific function RPTs are established in yeast.…”
Section: Discussionmentioning
confidence: 99%